Chinese Higher Education: The role of the economy and Projects 211/985 for system expansion - Danilo de Melo Costa; Qiang Zha (Ensaio, 2020)
China has experienced a significant economic growth in recent years. In addition, the country has also built the largest system of Higher Education in the world. However, was the economy that stimulated the advancement of Higher Education? Or was Higher Education that stimulated the advancement of the economy? To answer these questions, this research aimed to understand the role of economy and Projects 211 and 985 for the expansion of Chinese Higher Education. For that, an exploratory and qualitative research was developed, based on interviews with Chinese government managers and questionnaires applied to professors/specialists and to a student leadership. The results showed that investments in Higher Education were preponderant for the country’s economic growth, which was representative from a quantitative perspective. However, also aiming at qualitative growth, projects 211 and 985 were created, allocating a significant amount of resources to the selected institutions. Such positioning makes China an example of benchmarking for other countries that wish to progress economically and intellectually.